Dietary Patterns According To The Different Genetic Blood Groups - Madi, AlFaytouri Mohamed; Amhimmed, Wafa Khalleefah; Faraj, Emran AbdulKhaliq (International Journal of Scientific Research in Biological Sciences, 2023)
The blood is the most essential component of the human body. It accounts for about 8% of a normal human`s body. The negative or positive blood groups are A, B, AB, and O (rh). A drop of blood can have an enormous impact on a person`s life. One of the other factors that can affect a person`s life is nutrition. The concept of tailoring diets to match an individual`s genetic blood group has gained attention in recent years. Proponents argue that these personalized diets can optimize health and prevent disease. This paper aims to critically evaluate the scientific evidence supporting the relationship between genetic blood groups and dietary recommendations while emphasizing the importance of evidence-based approaches to healthy eating.